Large care gaps in primary care management of asthma: a longitudinal practice audit. Issue 1 (29th January 2019) - Price, Courtney; Agarwal, Gina; Chan, David; Goel, Sanjeev; Kaplan, Alan G; Boulet, Louis-Philippe; Mamdani, Muhammad M; Straus, Sharon E; Lebovic, Gerald; Gupta, Samir
Abstract : Objectives: Care gaps in asthma may be highly prevalent but are poorly characterised. We sought to prospectively measure adherence to key evidence-based adult asthma practices in primary care, and predictors of these behaviours. Design: One-year prospective cohort study employing an electronic chart audit. Setting: Three family health teams (two academic, one community-based) in Ontario, Canada. Participants: 884 patients (72.1% female; 46.0±17.5 years old) (4199 total visits; 4.8±4.8 visits/patient) assigned to 23 physicians (65% female; practising for 10.0±8.6 years). Main outcome measures: The primary outcome was the proportion of visits during which practitioners assessed asthma control according to symptom-based criteria. Secondary outcomes included the proportion of: patients who had asthma control assessed at least once; visits during which a controller medication was initiated or escalated; and patients who received a written asthma action plan. Behavioural predictors were established a priori and tested in a multivariable model. Results: Primary outcome: Providers assessed asthma control in 4.9% of visits and 15.4% of patients. Factors influencing assessment included clinic site (p=0.019) and presenting symptom, with providers assessing control more often during visits for asthma symptoms (35.0%) or any respiratory symptoms (18.8%) relative to other visits (1.6%) (p<0.01). Secondary outcomes: Providers escalated controller therapy in 3.3% of visits and 15.4% of patients. Factors influencing escalation included clinic site, presenting symptom and prior objective asthma diagnosis. Escalation occurred more frequently during visits for asthma symptoms (21.0%) or any respiratory symptoms (11.9%) relative to other visits (1.5%) (p<0.01) and in patients without a prior objective asthma diagnosis (3.5%) relative to those with (1.3%) (p=0.025). No asthma action plans were delivered. Conclusions: Major gaps in evidence-based asthma practice exist in primary care. Targeted knowledge translation interventions are required to address these gaps, and can be tailored by leveraging the identified behavioural predictors. Trial registration number: NCT01070095 ; Pre-results.